Predictors of development of atrial fibrillation in patients with obstructive sleep apnea without obesity - Andreieva, I. O.; Tokarenko, О. I.; Токаренко, Олександр Іванович (My University, 2020)
Aim: to assess the frequency of atrial fibrillation (AF) among patients with obstructive sleep apnea (OSA) without obesity and to define the predictors of AF in such category of patients.
Keywords: тези доповідей